Antioxidant Properties of Ethanol and Water Extracts of Different Parts of Salvia russellii Bentham Plant - Turkoglu, S.; Celik, S.; Turkoglu, I. (Asian Journal of Chemistry, 2011)
In this study, the antioxidant activity of water and ethanol extracts of Salvia russellii leaves and• (2,2'-azino-bis-(3-ethylbenzothiazoline-• (2,2-diphenyl-1-picrylhydrazyl)a-tocopherol. The extracts of Salvia russellii showed strong antioxidantSalvia russellii have effective antioxidant assay. This antioxidantSalvia russellii leaves and flowers is a potential flowers was evaluated by various antioxidant assay, ABTS 6-sulphonic acid)) radical scavenging capacity, DPPH radical scavenging capacity, superoxide anion radical scavenging capacity, hydrogen peroxide scavenging capacity, reducing power and metal chelating activities. Various antioxidant activities were compared to standard antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and activity. The extracts of property depends on concentration and increasing with increased amount of sample. The results obtained in the present study indicated that source of natural antioxidant.Salvia russellii leaves and• (2,2'-azino-bis-(3-ethylbenzothiazoline-• (2,2-diphenyl-1-picrylhydrazyl)a-tocopherol. The extracts of Salvia russellii showed strong antioxidantSalvia russellii have effective antioxidant assay. This antioxidantSalvia russellii leaves and flowers is a potential In this study, the antioxidant activity of water and ethanol extracts of flowers was evaluated by various antioxidant assay, ABTS 6-sulphonic acid)) radical scavenging capacity, DPPH radical scavenging capacity, superoxide anion radical scavenging capacity, hydrogen peroxide scavenging capacity, reducing power and metal chelating activities. Various antioxidant activities were compared to standard antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and activity. The extracts of property depends on concentration and increasing with increased amount of sample. The results obtained in the present study indicated that source of natural antioxidant.